Risk management and performance in the Balkans support contract - Greenfield, Victoria A.; Camm, Frank A. 1949- (RAND, 2005)
Is the Army getting what it needs and managing risks appropriately in its combat service support contracts? This report uses the Army's Balkans Support Contract and a continuous risk-management framework to answer these questions. On the basis of this case study, the authors conclude that the Army has been getting what it needs, though it might, at times, be bearing too much cost-related risk, and that few risks arise directly from the use of contractors. They also see a need for more training for the Army's contracting personnel to better plan, coordinate, and manage contracts.
"MG-282."
Includes bibliographical references
Keywords: United States -- Army -- Procurement -- Case studies; Geschichte 1900-2000; BUSINESS & ECONOMICS / Human Resources & Personnel Management; POLITICAL SCIENCE / Political Freedom & Security / General; POLITICAL SCIENCE / Political Freedom & Security / International Security; Wirtschaft; Defense contracts -- United States -- Case studies; Operation Allied Force, 1999 -- Equipment and supplies; Militärhilfe; USA; Bosnia and Hercegovina -- History, Military -- 20th century; Bosnia and Hercegovina -- History, Military -- 21st century; Bosnien-Herzegowina; Fallstudiensammlung